2014
DOI: 10.1590/0100-2945-345/13
|View full text |Cite
|
Sign up to set email alerts
|

Poliembrionia e potencial de obtenção de híbridos em citros

Abstract: A ocorrência de poliembrionia, elevada heterozigosidade e longo período pré-reprodutivo são os principais obstáculos à geração de variedades híbridas de citros. Este trabalho teve como objetivo a obtenção de indivíduos com potencial de uso como porta-enxertos através de cruzamentos entre diversas variedades. Observou-se que as hibridações envolvendo a tangerineira 'Sunki da Flórida' (TSKFL) como parental feminino possibilitaram a geração de maiores quantidades de híbridos, dando-se o contrário em relação àquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Soares Filho et al (2014) demonstrated that the degree of polyembryony is inversely proportional to the number of hybrids formed from controlled crosses. This demonstration was based on the results of crosses involving female parents with different degrees of polyembryony, which ranged from 8% to nearly 100% in 'Sunki Florida' mandarin, as verified in the following mandarins: 'Sunki Tropical' (94 %), 'Sunki Maravilha' (97%), 'Cleopatra' (98%) and 'Dancy' (99%) (C. tangerina Tanaka).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Soares Filho et al (2014) demonstrated that the degree of polyembryony is inversely proportional to the number of hybrids formed from controlled crosses. This demonstration was based on the results of crosses involving female parents with different degrees of polyembryony, which ranged from 8% to nearly 100% in 'Sunki Florida' mandarin, as verified in the following mandarins: 'Sunki Tropical' (94 %), 'Sunki Maravilha' (97%), 'Cleopatra' (98%) and 'Dancy' (99%) (C. tangerina Tanaka).…”
Section: Resultsmentioning
confidence: 99%
“…Polyembryony is a type of apomictic reproduction that is responsible for generating more than one embryo per seed (Chen et al 2008, Soares Filho et al 2014. This peculiarity allows the multiplication of interesting genotypes, especially in the case of rootstocks, by generating clones formed from the nucellar tissue of the mother plant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations